2016
DOI: 10.1038/ng.3530
|View full text |Cite
|
Sign up to set email alerts
|

A role for the bacterial GATC methylome in antibiotic stress survival

Abstract: Antibiotic resistance is an increasingly serious public health threat 1 . Understanding pathways allowing bacteria to survive antibiotic stress may unveil new therapeutic targets 2 -8 . We explore the role of the bacterial epigenome in antibiotic stress survival using classical genetic tools and singlemolecule real-time sequencing to characterize genomic methylation kinetics. We find that Escherichia coli survival under antibiotic pressure is severely compromised without adenine methylation at GATC sites. Whil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
98
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 95 publications
(105 citation statements)
references
References 75 publications
7
98
0
Order By: Relevance
“…Previous work focusing on both logarithmic phase growth and early stationary phase (no more than 24 h) has shown that GATC sites in the gammaproteobacteria are methylated by Dam to near completion (2628). To date, there has yet to be a characterization of methylation levels through late stationary phase, through death phase, and into long-term stationary phase.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous work focusing on both logarithmic phase growth and early stationary phase (no more than 24 h) has shown that GATC sites in the gammaproteobacteria are methylated by Dam to near completion (2628). To date, there has yet to be a characterization of methylation levels through late stationary phase, through death phase, and into long-term stationary phase.…”
Section: Resultsmentioning
confidence: 99%
“…1C). Many of the sites identified are located within genes that encode proteins involved in transport or transcriptional regulation or are located in the inner membrane (Table 1), and several of these sites were recently identified as being hypomethylated (28). Greater than 20% (14/66) of the sites are located within genes known to be regulated by CRP-cyclic AMP (cAMP) which binds a consensus sequence that contains GATC.…”
Section: Resultsmentioning
confidence: 99%
“…In addition, biological nanopores are able to discriminate not only the genome but also single base modifications such as 5-methylation of cytosine (5mC for DNA and m5C for RNA) and 6-methylation of adenine (6mA for DNA and 5mC for RNA) in native DNA/RNA[32]. Increasing evidence in last years suggests that DNA/RNA methylation can influence biological function, including regulation of DNA/RNA replication and repair, and gene expression[3336]. Recently, Oliveira et al reported that DNA methyltransterase in Clostridioides difficile has able to mediate sporulation, C. difficile disease transmission and pathogenesis[37].…”
Section: Introductionmentioning
confidence: 99%
“…Methylation plays important roles in epigenetic gene regulation in both eukaryotic and prokaryotic organisms. Compared with the explicit function of Dam methylation in mismatch repair, initiation of chromosome replication, transcription regulation at promoters containing GATC sequences, gene expression, pathogenicity and DNA stable under antibiotic pressure [19], there are limited details known regarding the function of the Dcm MTase [2]. The discovery of two of the three MTase genes on the IncA/C 2 plasmid were cytosine-specific was intriguing.…”
Section: Discussionmentioning
confidence: 99%